Analisis Kualitas Website PT Takdir Jaya Abadi Menggunakan Metode Webqual 4.0 Dan Importance Performance Analysis - Syahrul Aziz; Mery Oktaviyanti Puspitaningtyas; Yumi Novita Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
PT Takdir Jaya Abadi's website functions as a complete company information media, which includes information about company profiles and the industry sector currently engaged in, namely the optical disc replica services field. Since it was created in 2020, an evaluation has never been carried out, so the company does not know the quality of the website. Hence, it is necessary to evaluate PT Takdir Jaya Abadi's website. This study aims to determine whether the website meets user expectations using the Webqual 4.0 method and Importance Performance Analysis (IPA). The data obtained from 65 respondents showed a conformity analysis of 96% which stated that the user was not satisfied. The development of the gap analysis was -0.166, which means that the quality level is still not in line with user expectations. The results of the quadrant analysis that is a priority for website improvement are quadrant I with the attributes IF1, IF2, IT2, IT3 and IT4. These attributes are regarding up to date information, accurate information, a sense of security when accessing, a sense of security when conducting information search activities, and the safety of users' personal information.